Using Structural Equation Modelling to Predict Safety and Health Status among Stone Industries - Akbari, Hossein; Bahrami, Abbas; Dehghani Bidgoli, Sedighe; Karamali, Fahimeh; Hosseini, Ali (La Medicina del Lavoro, 2023)
Background: The creation of a working organization with a high safety level ensures employees’ health in their workplaces, therefore current study evaluated effect the organizational structure on the safety and health in the stone industry. Methods: The study was done among the 100 stone industries in Isfahan, Iran. We asked selected participants to complete the organizational structure questionnaire and ELMERI checklists. tested the hypothesis with Smart PLS 3.0. Results: The model fit index showed the standardized root mean square (SRMR=0.08), the normalized fit index (NFI=0.9), The coefficient of determination (R2 = 0.362), Effect size (ƒ2 was less than 0.2), and the Predictive relevance of the model (Q2=0.216) which is considered a good fit for mode. Also, the relation between formalization and health and safety was significant (β = -0.47). Conclusion: findings suggest that Organization factors are the basic reasons associated with occupational accidents and the main indicator of safety and health performance.